Pokko and the drum - Forsythe, Matthew, 1976- (Simon & Schuster Books for Young Readers, An imprint of Simon & Schuster Children's Publishing Division, 2019)
When Pokko plays her drum in the forest she suddenly finds herself surrounded by an entire band of animal musicians.